Model Pemrograman Linier untuk Memaksimalkan Laba Disertai Analisis Dual: Sebuah Kasus pada Agroindustri Kreatif Roti di Desa Keduanan Kecamatan Depok Kabupaten Cirebon - Siti Aulia Dwi Maulidah; Andung Rokhmat Hudaya; Bobby Rachmat Saefudin (Ma'soem University, 2021)
In an effort to maximize production profits, companies often face constraints that come from the resources used in the production process. Moreover, companies that produce more than one type of product are required to be able to make optimization efforts in determining the level of production that can achieve maximum profit with limited available resources. This study aims to analyze the most optimal combination of production levels to maximize profits from four types of sweet breads produced based on 3 resource constraints, namely the availability of raw materials, direct labor hours and machine working hours; and perform a dual analysis on each resource. This research was conducted in Keduanan Village, Depok District, Cirebon Regency in a creative agro-industry company called Roti Wakwaw. The design of this study is a quantitative design with the interview method using a questionnaire to 7 people consisting of one company owner and six employees. Data analysis tools using linear programming and dual analysis. The results of the research include an optimum model that increases profits with an additional profit of Rp. 129,700 per one day of production from the actual profit. The results of the dual analysis show that all resources are in excess and inactive, except for sugar as raw materials which are rare and positive.